Fostering a Bullying-Free School Environment: The Role of Principals’ Spiritual Leadership in Primary Education - Rd Furqon; Diding Nurdin (AL-ISHLAH: Jurnal Pendidikan, 2025)
Bullying remains a persistent issue in many schools, negatively impacting student well-being and academic performance. This study explores the role of spiritual leadership in promoting a bullying-free, inclusive school culture that supports effective teaching and learning at SDIT Irsyadur Rahman. A qualitative descriptive method was employed using a case study approach. Participants were selected through purposive sampling and included the principal (as the primary leader), two senior teachers (as co-principals), and two students who experienced the effects of the school’s spiritual leadership. Data were collected through structured interviews, observation, and documentation, and validated using triangulation techniques. The data were analyzed using Atlas.ti version 9. Findings revealed that spiritual leadership practiced by the principal played a significant role in fostering a positive school culture. It contributed to a supportive and inclusive environment where bullying was effectively minimized, and respectful social interactions were encouraged. The principal’s spiritual leadership fostered values such as empathy, respect, and cooperation among students and staff, which collectively helped in reducing instances of bullying and enhancing the overall school climate. Spiritual leadership is a critical component in establishing a positive, bullying-free school environment. The outcomes of this study can serve as a valuable reference for school leaders aiming to improve social dynamics and support effective educational practices.